Pregnancy loss among Muslim women: A narrative review - Khadijat K. Adeleye; Oluwabunmi Ogungbe; Muhammad Chutiyami; Favorite Iradukunda (Elsevier, 2024)
Background: Diversity in spirituality, religion, and cultural norms among women leads to varying attitudes, grieving processes, and coping mechanisms after a pregnancy loss. Despite this, there is a limited understanding of grief, coping mechanisms, and mental health outcomes following pregnancy loss among Muslim women. Objectives: This study aims to examine the impact of religion, spirituality, and faith communities on the psychological health of Muslim women during pregnancy loss. Method: We systematically searched six databases with the key concepts, 'pregnancy loss' and 'Muslim women,' in PubMed, CINAHL, Embase, Web of Science, APA PsycINFO, and Academic Search. The search strategy was developed in line with the PCOT framework: Population - Muslim Women with ''pregnancy loss,'' ''miscarriage,'' ''stillbirth, Context - ''religion,'' faith, ''spirituality,'' ''faith communities,'' Outcome - "religious practices," perception, coping mechanism, ''psychological health.''Studies were screened, their quality appraised, and narratively sized in line with the review aim. The review protocol was registered at Open Science Framework (OSF): https://doi.org/10.17605/OSF.IO/52QTA. Result: Findings from the reviewed articles addressed the following themes: (a) Overwhelming Grief and Loss, (b) social isolation and stigmatization, (c) impact on mental health, and (d) trust in divine destiny. Islamic beliefs were strongly featured in how Muslim women processed pregnancy loss. Concepts such as tawakkul and yaqeen (trusting and certainty) were used to interpret pregnancy loss, with many women acknowledging that their Islamic faith eased the sorrow of pregnancy loss, facilitated acceptance, and strengthened their Islamic belief system. Conclusion: This review revealed that there is limited information on Muslim women's experience of pregnancy loss. Professionals helping Muslim women dealing with the grief of pregnancy loss need to be aware that spirituality and faith communities play a major role in shaping their coping mechanisms. Future studies on the development of culturally congruent bereavement care models and supportive interventions for Muslim women facing pregnancy loss.